2019
DOI: 10.1051/0004-6361/201834379
|View full text |Cite
|
Sign up to set email alerts
|

Consistent cosmic shear in the face of systematics: a B-mode analysis of KiDS-450, DES-SV and CFHTLenS

Abstract: We analyse three public cosmic shear surveys; the Kilo-Degree Survey (KiDS-450), the Dark Energy Survey (DES-SV) and the Canada France Hawaii Telescope Lensing Survey (CFHTLenS). Adopting the 'COSEBIs' statistic to cleanly and completely separate the lensing E-modes from the non-lensing B-modes, we detect B-modes in KiDS-450 and CFHTLenS at the level of ∼ 2.7σ. For DES-SV we detect B-modes at the level of 2.8σ in a non-tomographic analysis, increasing to a 5.5σ B-mode detection in a tomographic analysis. In or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 92 publications
3
41
0
Order By: Relevance
“…Hence we expect a pattern in the c 1 -bias that corresponds to the detector layout. Asgari et al (2019) showed that such a repeating pattern can lead to B-modes in the ellipticity distribution and found a hint of such a pattern in the KiDS-450 data. In combination with the findings about OmegaCam discussed above we decided to correct for such a repeating pattern in the data.…”
Section: Additive Shear Measurement Biasmentioning
confidence: 91%
See 1 more Smart Citation
“…Hence we expect a pattern in the c 1 -bias that corresponds to the detector layout. Asgari et al (2019) showed that such a repeating pattern can lead to B-modes in the ellipticity distribution and found a hint of such a pattern in the KiDS-450 data. In combination with the findings about OmegaCam discussed above we decided to correct for such a repeating pattern in the data.…”
Section: Additive Shear Measurement Biasmentioning
confidence: 91%
“…The Joudaki et al (2018) and Troxel et al (2018a) approach tried to correct for this but instead biases ξ ± low to a similar degree and hence S 8 is biased high. Here we integrate ξ ± over each θ bin, which yields results that correspond to the red lines in figure A.1 of Asgari et al (2019). This unbiased approach has the disadvantage of requiring an additional integration in the likelihood.…”
Section: Cosmic Shear Signalmentioning
confidence: 99%
“…In addition, we advocate the use of a different set of statistics, 'Ψ-statistics', based on the Complete Orthogonal Sets of E/B-Integrals (COSEBIs, Schneider et al 2010). COSEBIs are statistics designed for cosmic shear analysis which are able to minimise the effect of small physical scales, while staying clear of the measurement challenges of Fourier space statistics (Asgari et al 2019(Asgari et al , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, one of the most challenging systematic uncertainties is the characterization of the redshift distribution of the weak lensing tomographic samples, which contain millions of faint galaxies with a few colours measured using broad-band filters. A correct description of such redshift distributions is crucial to avoid introducing a bias in the cosmological inference (Huterer et al 2006;Cunha et al 2012;Hildebrandt et al 2012;Benjamin et al 2013;Huterer, Cunha & Fang 2013;Bonnett et al 2016;Hildebrandt et al 2017;Joudaki et al 2017;Hoyle et al 2018;Joudaki et al 2019) and to allow a robust comparison between cosmological parameters from weak lensing analysis and from the cosmic microwave background (CMB, Planck Collaboration VI 2018), especially when a number of recent studies suggest a mild tension between the values of cosmological parameters inferred for the early and late-time universe (Asgari et al 2019;Joudaki et al 2019;Wright et al 2020) The really large area and depth covered by these surveys makes it unfeasible to measure spectroscopic redshifts for each galaxy of interest, which is why a number of alternative techniques have been developed over the years to estimate their redshift distributions. These can be broadly grouped as those which use angular cross-correlations with an overlapping tracer sample with well-characterized redshifts (clustering redshifts, see Newman 2008;Ménard et al 2013;Schmidt et al 2013;Davis et al 2017;Hildebrandt et al 2017;Gatti et al 2018), those that model the galaxy spectral energy distribution (SED) of each galaxy to connect their observed colours to redshift (e.g.…”
mentioning
confidence: 99%